Relationship between temporomandibular disorders and orthodontic treatment: a literature review - Ronaldo Antônio Leite; Joacir Ferreira Rodrigues; Maurício Tatsuei Sakima; Tatsuko Sakima (Dental Press Journal of Orthodontics, 2013)
OBJECTIVE: The objective of this study was to review the most recent studies from the last 15 years, in search of clinical studies that report the relationship between TMD and orthodontic treatment and/or malocclusion. Our intention was to determine whether orthodontic treatment would increase the incidence of signs and symptoms of TMD, and whether orthodontic treatment would be recommended for treating or preventing signs and symptoms of TMD. METHODS: Literature reviews, editorials, letters to the editor, experimental studies in animals and short communications were excluded from this review. Were included only prospective, longitudinal, case-control or retrospective studies with a large sample and significant statistical analysis. Studies that dealt with craniofacial deformities and syndromes or orthognathic surgery treatment were also excluded, as well as those that reported only the association between malocclusion and TMD. RESULTS: There were 20 articles relating orthodontics to TMD according to the inclusion criteria. The studies that associated signs and symptoms of TMD to orthodontic treatment showed discrepant results. Some have found positive effects of orthodontic treatment on signs and symptoms of TMD, however, none showed a statistically significant difference. CONCLUSIONS: All studies cited in this literature review reported that orthodontic treatment did not provide risk to the development of signs and symptoms of TMD, regardless of the technique used for treatment, the extraction or non-extraction of premolars and the type of malocclusion previously presented by the patient. Some studies with long-term follow-up concluded that orthodontic treatment would not be preventive or a treatment option for TMD. OBJETIVO: revisar a literatura mais atual, dos últimos 15 anos, em busca de estudos clínicos que relatem a relação entre a disfunção temporomandibular (DTM) e o tratamento ortodôntico e/ou a má oclusão. A intenção foi verificar se o tratamento ortodôntico aumentaria o aparecimento de sinais e sintomas de DTM, e se o tratamento ortodôntico seria um recurso para o tratamento ou prevenção dos sinais e sintomas de DTM. MÉTODOS: artigos dos tipos revisão de literatura, editorial, carta, estudo experimental em animais e comunicação foram excluídos dessa revisão. Foram incluídos artigos prospectivos, longitudinais, caso-controle ou retrospectivo com amostra maior, com relevante análise estatística. Estudos que abordassem deformidades e síndromes craniofaciais e tratamento por cirurgia ortognática também foram excluídos, bem como aqueles que relatassem apenas a associação entre má oclusão e DTM. RESULTADOS: foram encontrados 20 artigos relacionando Ortodontia à DTM, segundo os critérios adotados. Os estudos, então, associando sinais e sintomas de DTM ao tratamento ortodôntico apresentaram resultados heterogêneos. Alguns encontraram efeitos positivos do tratamento ortodôntico para os sinais e sintomas de DTM; entretanto, nenhum deles apresentou diferença estatisticamente significativa. CONCLUSÕES: todos os estudos citados nessa revisão de literatura relataram que o tratamento ortodôntico não forneceu risco ao desenvolvimento de sinais e sintomas de DTM, independentemente da técnica utilizada para tratamento, da exodontia ou não de pré-molares e do tipo de má oclusão previamente apresentada pelo paciente. Alguns estudos realizados com acompanhamento em longo prazo concluíram que o tratamento ortodôntico não seria preventivo ou uma modalidade de tratamento para DTM.